Przyczynek do dyskusji na temat kompozycji Dziejów Apostolskich - Rakocy, Waldemar (The Biblical Annals, 2017)
In keeping with many opinions on the construction of the Acts of the Apostles the present paper seeks to put forward a new approach to these problems. Geographical information in Acts 1:8 plays here an important role, but is not understood too literary. Two big units may be distinguished in the Book, into which it is divided in the summary in 8:1b-3. The first is situated in Jerusalem and deals with Judaism, with which the majority of authors agree. Narration related with the departure of the Gospel beyond Jerusalem is more difficult. Three units are distinguished here: 8:4-11, 18; 11:19-20,38; 21:1-28:31. The first plays the preparatory role toward the proper narration relating the preaching of the Gospel all over the world. The themes which have been foretold in it are developed in section 11:19-20:38, which speaks solely about Christ’s preaching to Jews and Greeks (the Gentiles) alike. The third section, 21:1-28:31, presents Apostle Paul as a witness in chains because of Israel’s hope, which he preaches. In favor of such a construction of the Book of the Acts are numerous literary and thematic hints, which make us distinguish the said sections in it.